Elevated blood urea nitrogen is associated with recurrence of post-operative chronic subdural hematoma - Ning Wang; Jiangnan Hu; Anthony Oppong-Gyebi; Xuanhao Zhu; Yihao Li; Jianjing Yang; Linhui Ruan; Qichuan Zhuge; Sheng Ye (BMC Neurology, 2020)
Abstract Background Chronic subdural hematoma (CSDH) is fundamentally treatable with about a 2–31% recurrence rate. Recently, there has been renewed interest in the association between Blood Urea Nitrogen (BUN) and intracranial lesion. Therefore, this paper attempts to show the relationship between BUN and CSDH recurrence. Methods A total of 653 CSDH cases with Burr-hole Irrigation (BHI) were enrolled from December 2014 to April 2019. The analyzed parameters included age, gender, comorbidities, laboratory investigations, medication use and hematoma location. The cases were divided into recurrence and non-recurrence groups while postoperative BUN concentration was further separated into quartiles (Q1 ≤ 4.0 mmol/L, 4.0 < Q2 ≤ 4.9 mmol/L, 4.9 < Q3 ≤ 6.4 mmol/L, Q4 > 6.4 mmol/L). Restricted cubic spline regressions and logistic regression models were performed to estimate the effect of BUN on CSDH recurrence. Results CSDH recurrence was observed in 96 (14.7%) cases. Significant distinctions were found between recurrence and non-recurrence groups in postoperative BUN quartiles of cases (P = 0.003). After adjusting for the potential confounders, the odds ratio of recurrence was 3.069 (95%CI =1.488–6.330, p = 0.002) for the highest quartile of BUN compared with the lowest quartile. In multiple-adjusted spline regression, a high BUN level visually showed a significantly high OR value of recurrence risk. Conclusions Elevated BUN at post-operation is significantly associated with the recurrence of CSDH, and it is indicated that high levels of serum BUN after evacuation may serve as a risk factor for CSDH recurrence.